Photoluminescence of bulks and thin films of Eu3+-doped organic/inorganic hybrids - Pecoraro, Édison [UNESP]; Ferreira, R. A. Sa; Molina, C. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Messsaddeq, Y. [UNESP]; Carlos, L. D. (Elsevier B.V. Sa, 2008)
Organic-inorganic hybrids formed by polyether-based chains grafted to both ends to a siliceous backbone through urea cross-linkages (-NHC=O)NH-), named di-ureasil, have been used as host for incorporation of Eu3+ in the form of EuCl3. The bulks and the thin films, both optically transparent, were characterized by excitation, absorption and emission spectroscopy. Photoluminescence results point out that the Eu3+ ions occupy, at least, two distinct local environments. Besides, the processing method (thin films or bulks) has influence on the energy levels of the hybrid host probably due to the lower degree of organization of the thin films structure. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: europium; photoluminescence; organic-inorganic hybrids; thin films